2006
DOI: 10.2174/138920006776359284
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Intermediates and the Pathogenesis of Adverse Drug Reactions: The Toxicology Perspective

Abstract: Severe adverse drug responses are infrequent but occasionally serious events that are not readily predictable at the preclinical development level using only non-human or in vitro models. A common characteristic of the more serious toxicities is generation of short-lived and highly reactive electrophilic species in some individuals. The objective here is to review the literature for toxicological mechanisms that underlie known adverse drug reactions and then categorize the biological consequences of reactive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 106 publications
0
15
0
Order By: Relevance
“…Our recent studies have identified excessive apoptosis of neutrophil progenitors as the likely underlying cause of this maturation arrest in patients with Kostmann disease [16]. Our patients did not display the Kostmann phenotype prior to lymphoma diagnosis and are therefore unlikely to harbor homozygous HAX1 mutations; however, a hypothesis that has been advocated recently, is that heterozygous, and hence clinically silent, mutations can constitute a risk factor for idiosyncratic drug reactions, often classified as toxic [25,26]. For this reason, we performed HAX1 mutation analyses in all four cases.…”
Section: Discussionmentioning
confidence: 62%
“…Our recent studies have identified excessive apoptosis of neutrophil progenitors as the likely underlying cause of this maturation arrest in patients with Kostmann disease [16]. Our patients did not display the Kostmann phenotype prior to lymphoma diagnosis and are therefore unlikely to harbor homozygous HAX1 mutations; however, a hypothesis that has been advocated recently, is that heterozygous, and hence clinically silent, mutations can constitute a risk factor for idiosyncratic drug reactions, often classified as toxic [25,26]. For this reason, we performed HAX1 mutation analyses in all four cases.…”
Section: Discussionmentioning
confidence: 62%
“…Reactive metabolites should bind covalently to biological macromolecules, such as proteins, nucleic acids and lipids, to modify these biological macromolecules irreversibly, which may trigger an allergic reaction, cell disorder, organ injury or carcinogenicity in the case of DNA damage [2,3]. We previously reported that electrochemical oxidation of troglitazone (TGZ, Scheme 1) in an aqueous medium generated p-quinone derivative (TGZQ), which is identical to a metabolite of TGZ found in human plasma after administration [4]; however, TGZQ was not a reactive metabolite.…”
Section: Introductionmentioning
confidence: 99%
“…Chemically reactive electrophiles can also covalently react with nucleic acids on the DNA thereby causing changes in DNA structure or gene expression. Changes in DNA can lead to mutagenicity, teratogenicity or carcinogenicity 1316…”
Section: Reactive Metabolitesmentioning
confidence: 99%